The PACT Study: results of a time series study investigating the impact, acceptability and cost of an integrated model for psychosocial screening, care and treatment of patients with urological and head and neck cancers. Issue 4 (25th October 2021) - Girgis, Afaf; Candler, Hayley B.; Handley, Tonelle; Descallar, Joseph; Hansen, Vibeke; Haas, Marion; Viney, Rosalie; Haywood, Philip; Bellamy, Douglas; Proietto, Anthony; Kelly, Brian J.
Abstract: Background: The significant psychosocial morbidity experienced by cancer patients is often undetected and untreated. Despite international priority given to psychosocial care for cancer patients, implementation of psychosocial programs into routine cancer care is limited. We developed, implemented, and assessed the impact, acceptability, and cost of an integrated, patient-centered Psychosocial Assessment, Care and Treatment (PACT) model of care for cancer patients within a general hospital setting. Methods: A time series research design was implemented to test the PACT model of care, newly introduced in an Australian tertiary hospital. System-level impact on systematic distress screening and management was assessed through audit of the medical records of three cross-sectional samples of 141 patients, at baseline and at 12 and 24 months post-baseline. The impact of the model on patient experience and health care professionals' (HCPs) knowledge and confidence was assessed via surveys. The acceptability of the intervention was assessed through HCP interviews at 24 months. The cost of the intervention was assessed by PACT staff recording the time spent on care provision, training, and intervention administration, and associated costs were calculated using staff payment rates adjusted for superannuation and leave. Results: Across the 24 months of implementation, formal distress screening increased from 0% at baseline to 29% of patients at 12 months and 31% of patients at 24 months, with an associated decrease in informal screening as formal screening increased. There was no notable change in distress management (ie, development of care plans) across the time period. Baseline patient experience was already high (mean score = 46.85/55) and did not change significantly over the course of the study. In both general and specific areas of addressing patient psychosocial concerns, HCP knowledge and confidence was moderate and remained largely unchanged over the course of the study. HCPs perceived the PACT model as highly beneficial and instrumental in bringing about significant changes to staff's knowledge, practices and awareness of psychosocial issues. The estimated total labor cost (including on-costs) was AUD$119, 239 (over the 2 years); with a declining cost over the lifetime of the intervention reflecting the higher initial set-up costs. Conclusions: Although the PACT model was associated with an increase in distress screening, staff workloads, high turnover, and administrative barriers may have restricted the translation into distress management. Future research exploring effective avenues to engage staff at a management level and ensure that staff view distress management as a valuable component of their role may assist to embed strategies into the general hospital culture and lead to more sustainable changes.